(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
The HEPA Europe network recognizes that climate change and the loss of biodiversity are urgent threats to the health of humans, animals, and the planet. As a network devoted to improving health and wellbeing through physical activity, we acknowledge our responsibility to minimize our environmental impact and to engage, among other topics, in research on the interconnections between physical activity, climate change, and planetary health and wellbeing. HEPA Europe strives to lead by example in aligning with the 1.5-degree Celsius goal of the 2015 COP Paris Agreement. Action on increasing planetary health and wellbeing is integral to promoting sustainable, healthy lives now and for future generations.